International Perspectives on Writing Curricula and Development A Cross-Case Comparison - Jeffery, Jill; Parr, Judy (Taylor & Francis, 2021)
writing studies, writing development, cross-national writing research, school writing, curricular analysis, curriculum, assessment tools, national education